2013
DOI: 10.5539/ibr.v6n5p69
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of User Attitudes to SNS

Abstract: Social Networking Service (SNS) have become widely used in Japan in recent years with Facebook, mixi and Twitter being the most popular. These are used in various fields of life together with the convenient devices such as smart-phones. A questionnaire investigation was used to clarify the current usage condition, issues and desired function etc. Information for marketing purposes was then extracted. Fundamental Statistical Analysis, Multi Corresponding Analysis, Quantitative Analysis and Text Minig Analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The results of our study also revealed similarities and differences amongst German, Polish, and Russian consumers. The literature review indicated that fb is a platform that is used mainly for communication activities -especially for communication with friends and families (Ellison, Steinfield, and Lampe 2007;Ross et al 2009, Aburai, Ishii, andTakeyasu 2013;Davies, Musango, and Brent 2016). Our study confirmed these results.…”
Section: Conclusion and Managerial Implicationssupporting
confidence: 82%
See 1 more Smart Citation
“…The results of our study also revealed similarities and differences amongst German, Polish, and Russian consumers. The literature review indicated that fb is a platform that is used mainly for communication activities -especially for communication with friends and families (Ellison, Steinfield, and Lampe 2007;Ross et al 2009, Aburai, Ishii, andTakeyasu 2013;Davies, Musango, and Brent 2016). Our study confirmed these results.…”
Section: Conclusion and Managerial Implicationssupporting
confidence: 82%
“…Within the context of this paper, the focus is on Facebook, YouTube, and vkontakte as the tools that are used in cmc. Facebook was designed to permit students to communicate with each other (Aburai, Ishii, and Takeyasu 2013), send materials, and search for different types of information (Krasnova et al 2012). Ellison, Steinfield, and Lampe (2007) showed that Facebook is an effective tool for communicating amongst friends or family's members, but it is not a significant tool which is used to meet new people.…”
Section: Sns In Communication (C) Within the Context Of Cmc Theorymentioning
confidence: 99%